Circulating Endothelial Cells and Microparticles as Prognostic Markers in Advanced Non-Small Cell Lung Cancer - Fleitas, Tania; Martínez-Sales, Vicenta; Vila, Virtudes; Reganon, Edelmiro; Mesado, David; Martín, Maria; Gómez-Codina, José; Montalar, Joaquín; Reynés, Gaspar (PLOS ONE, 2012)
Background Circulating endothelial cells and microparticles have prognostic value in cancer, and might be predictors of response to chemotherapy and antiangiogenic treatments. We have investigated the prognostic value of circulating endothelial cells and microparticles in patients treated for advanced non-small cell lung cancer. Methodology/Principal Findings Peripheral blood samples were obtained from 60 patients before first line, platinum-based chemotherapy +/− bevacizumab, and after the third cycle of treatment. Blood samples from 60 healthy volunteers were also obtained as controls. Circulating endothelial cells were measured by an immunomagnetic technique and immunofluorescence microscopy. Phosphatidylserine-positive microparticles were evaluated by flow cytometry. Microparticle-mediated procoagulant activity was measured by the endogen thrombin generation assay. Results: pre- and posttreatment levels of markers were higher in patients than in controls (p<0.0001). Elevated levels of microparticles were associated with longer survival. Elevated pretreatment levels of circulating endothelial cells were associated with shorter survival. Conclusions/Significance Circulating levels of microparticles and circulating endothelial cells correlate with prognosis, and could be useful as prognostic markers in patients with advanced non-small cell lung cancer.